Junior athletes' goal orientation, motivation, and emotional and physical exhaustion - Moen, F.; Federici, R. A. (International Journal of Coaching Science, 2014)
Despite the considerable concern regarding burnout in sports, there has been a paucity of research investigating burnout`s relation to goal orientation and motivation. The purpose of the present study was therefore to explore a theoretical model of correlations between goal orientation, motivation, and emotional and physical exhaustion (a dimension of burnout) among junior athletes in elite sports gymnasiums in Norway. The theoretical model proposed that mastery goal orientation was positively and directly related to intrinsic motivation and negatively related to extrinsic motivation and exhaustion. Performance goal orientation was expected to be inversely related. Additionally, extrinsic motivation was expected to be positively related to exhaustion, whereas intrinsic motivation was expected to be negatively related. The results in this study partially confirm the proposed theoretical model. Mastery orientation was positively related to intrinsic motivation and negatively related to extrinsic motivation. However, mastery orientation was only indirectly related to exhaustion, mediated by intrinsic and extrinsic motivation. The analyses revealed identical but inverse patterns for performance orientation.